HUBUNGAN PEMBERIAN SUSU FORMULA BAYI USIA 12-23 BULAN DENGAN PERTUMBUHAN BATITA DI DESA PRINGGASELA WILAYAH KERJA PUSKESMAS PRINGGASELA UTAMA - R. Supini; Gima Sevila Paramitha (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
The baby's growth and development process determines the future of children as the next generation of the nation's future, so attention to the state of nutrition and health is important Around 40% of children in rural areas experience stunted growth. According to the World Health Organization (WHO) estimates the cause of one-third of deaths of toddlers worldwide is due to malnutrition. For Southeast Asia, which is the region that has the largest prevalence of malnutrition in the world, which is 42%, (Unicef, 2015). This research aims to find out